Vermicompost for Mitigation of Surfactant Contamination in Surface Water - Islam, M. A.; Sarker, S.; Nasrin, M. S.; Hoque, M. A.; Islam, M. S.; Islam, M. N. (Journal of Scientific Research, 2020)
Surfactants are the most important pollutants of surface water which should be removed for the safety of aquatic life. The potentiality of vermicompost for the removal of surfactant contamination in surface water was studied by measuring surfactant concentration, pH and conductivity for nine days in six trials with different proportions of soil, vermicompost and phosphate keeping the surfactant concentration constant. The trials T1, T2, T3, T4 and T5 were considered as simulated ponds and T0 as control. The surfactant concentration, electrical conductivity and pH were found to change upon the application of vermicompost. The surfactant degradation rate of vermicompost amended systems was significantly higher than the control system. Surfactant was almost completely depleted in vermicompost amended systems within the monitoring period. The presence of phosphate increases the surfactant removal efficacy of vermicompost. The pH values for vermicompost amended systems were almost constant near 7. The electrical conductivity of vermicompost amended systems was found to increase with time whereas that for the control systems was almost constant. Therefore, vermicompost can be considered as an excellent amendment as they have the ability to remove surfactant in surface water correcting the pH and increasing the availability of nutrients of the systems.